The business of birth control : contraception and commerce in Britain before the Sexual Revolution - Jones, Claire (Museum director); Manchester University Press (Manchester, UK : Manchester University Press, 2020)
This volume provides a new commercial perspective on contraception in modern Britain. It examines contraceptives as commodities and demonstrates the significance of the contraceptive industry in shaping sexual knowledge alongside the medical profession, the birth control movement, and the state before the emergence of the contraceptive pill.
Machine generated contents note: 1. The dynamics of production: contraceptive manufacturing -- 2. Shaping markets: packaging, brands and trademarks -- 3. The print culture of contraceptives: advertising and the circulation of birth control knowledge -- 4. `As honest as business permits': medical practitioners, birth control clinics and contraceptive efficacy -- 5. Over the counter and on the high street: contraceptive retailing in the urban landscape.
Made available via: manchesterhive.
MUP 2020 titles.
In English.
Includes bibliographical references (pages 215-238) and index.
JSTOR
Keywords: Contraception -- Great Britain -- History -- 20th century; Birth control -- Economic aspects -- Great Britain -- History; Contraception -- Technological innovations -- Great Britain -- History; Public health -- Economic aspects -- Great Britain -- History; Great Britain -- History -- 20th century; Contraception -- history; Public Policy -- history; Contraceptive Devices -- history; Contraceptive Devices -- economics; History, 20th Century; United Kingdom; Contraception -- Grande-Bretagne -- Histoire -- 20e siècle.; Régulation des naissances -- Aspect économique -- Grande-Bretagne -- Histoire; Contraception -- Innovations -- Grande-Bretagne -- Histoire; Santé publique -- Aspect économique -- Grande-Bretagne -- Histoire; Grande-Bretagne -- Histoire -- 20e siècle.; Médecine -- Histoire -- 20e siècle.; Birth control -- Economic aspects; Contraception; Contraception -- Technological innovations; Public health -- Economic aspects; Great Britain; HISTORY / Social History; 1900-1999; History